Romania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper estimates a small open economy model that makes it possible to quantify the relative strength of the trade and financial channels in Hungary, Poland. and Romania. The Bayesian results indicate that both the trade and financial channels are strongest for Romania, possibly owing to the expansion of financial balance sheets and lower integration into global supply chains. For all countries, tighter domestic monetary conditions result in reduction of output and currency appreciation, although the magnitude of appreciation is less in Romania compared with peers. The trade channel is also dominant in the transmission of foreign monetary policy shocks, which result in output losses and currency depreciation.